IMPACT OF SALT STRESS ON PLANT GROWTH AND APPROACHES FOR ENHANCED TOLERANCE - KHALID, S; CHAUDHARY, N; IRUM, A; AAS, MA; NOOR, S; MUNSHA, A; TOOR, S; IQBAL, RJ; HUSSAIN, MI; FAROOQ, MS (Biological and Clinical Sciences Research Journal, 2024)
Salt stress is a major environmental factor that limits plant growth and productivity, particularly in regions with high soil salinity. As salt accumulation disrupts cellular functions, plants face challenges in water uptake, nutrient absorption, and maintaining metabolic processes, leading to reduced yield and crop quality. Plants have developed several mechanisms of salt tolerance, including ion homeostasis, osmotic adjustment, and antioxidant defense, which help plants adapt to saline conditions. Soil management techniques, such as leaching and the use of amendments, alongside plant growth regulators and microbial inoculants, can enhance plant resilience to salinity. There is a dire need for interdisciplinary research to understand the complex interactions between plants, soil, and microorganisms, as well as the need to develop salt-tolerant crop varieties through genetic engineering. Rising temperatures and sea levels due to climate change have exacerbated salinity issues. Long-term solutions, such as soil reclamation and sustainable water management, are crucial to ensuring the future of agriculture in saline-prone regions.